Arbitral autonomy and applicable and overriding law. Issue 1 (2nd January 2019) - Mance, Jonathan
ABSTRACT: This article examines themes associated with the role of arbitration and its interrelationship with the law generally. These include the extent to which parties to an arbitration agreement are free to choose the principles governing the procedural and substantive aspects of the arbitration. The article considers the circumstances in which such a choice may be affected or overridden by mandatory principles of law or court intervention, by the courts of the seat of arbitration or in enforcement proceedings in another jurisdiction. It identifies the potential tension between the interests of party and arbitral autonomy on the one hand, and the public policy which justifies court interventions in the arbitral process and governs enforcement of awards on the other. The tension has in a European context manifested itself recently in a marked dichotomy between the attitudes of European Union law to commercial arbitration and to bilateral investment treaty arbitration, presenting arbitrators and courts involved in the latter with potential dilemmas. It suggests that there is still scope for holistic development, recognizing the value attached to arbitration by the commercial community.